Detection of Plant Viruses in Some Ornamental Plants That Act as Alternate Hosts (The Agriculturists, 2012)
A study was conducted at the Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU), Salna, Gazipur to detect virus infecting ornamental plants. Enzyme-linked Immunosorbant Assay (ELISA) and symptomalogy were used for detection. Five viruses namely TPVV (Tomato Purple Vein Virus), CMV-Y (Cucumber Mosaic Virus-Y), OYVCMV (Okra Yellow Vein clearing Mosaic Virus), MYMV (Mung bean Yellow Mosaic Virus), TYLCV (Tomato Yellow Leaf Curl Virus) were detected on Tagetes erecta (Marigold), Salvia splendens (Salvia), Dahlia hybrida (Dahlia), Helichrysum bracteatum (Straw flower), Impatiens balsamina (Garden balsam). CMV-Y caused mosaic of Dahlia and Leaf Curl of Marigold. MYMV caused Yellow Mosaic of Dahlia hybrid, while TYLCV caused mosaic of Helichrysum bracteatum. OYVCMV produced leaf chlorosis on Salvia splendens, and chlorotic spots on Impatiens balsamina. TPVV caused purple leaf on Tagetes erecta DOI: http://dx.doi.org/10.3329/agric.v10i2.13141 The Agriculturists 2012; 10(2) 46-54